EFFICIENCY ANALYSIS OF FORMATION AND IMPLEMENTATION THE UNITED TERRITORIAL COMMUNITIES BUDGET PROGRAMS - Myhovych, T.M. (The actual problems of regional economy development, 2018)
The article is directed to study the peculiarities of planning and implementation the local budgets in conditions of decentralization. The author defines the essence of budget programs as a special component of the program-target method. The method of comparative analysis the effectiveness of the budget programs executed by spending units of local budgets is analyzed; its position was used to evaluate budget programs operating in the territory of the united territorial community. The shortcomings of the corresponding methodology are generalized and the directions of improvement the mechanism for analysis the effectiveness of the formation and implementation the joint territorial communities budget programs are outlined.